A study into "organisational readiness" and its impacts on school improvement. Issue 2 (4th February 2019) - Lynch, David; Smith, Richard; Yeigh, Tony; Provost, Steve
Abstract : Purpose: The purpose of this paper is to compare measures of socio-economic status (Index of Community Socio-educational Advantage values (ICSEA)), school performance, school funding and school readiness in terms of their impact on student performance. In this respect, the paper tests the proposition – given research that suggests the teacher is the important ingredient in improved student learning performance – that a school principal who has strategical worked to "ready" their teachers for a whole of school teaching improvement agenda will generate increased student learning results than those who have not and further this improvement will occur irrespective of the circumstance of the socio-economic circumstance of the school. Design/methodology/approach: In total, 22 Government schools from a single school district in Australia participated in the study, after having been involved in a system sponsored "teaching improvement program". A survey, consisting of 30 seven-point Likert-style scale items, was administered to all teachers and school leaders in the school district. The survey was designed to rate levels of staff perceived alignment, capability and engagement to the programme as it was implemented by the Head in each school. The information regarding each school's ICSEA value, funding per student and student learning performance, was obtained from the database provided by the relevant authority (ACARA). All statistical analysis was completed using SPSS Version 22. Findings: The findings of this study indicate that high levels of organisational readiness, as defined by the alignment, capability and engagement (ACE) approach, are associated with effective teaching and improvement in student outcomes. In turn, the authors interpret this to mean that the internal organisation of a school has important effects on student achievement that are independent to external factors such as school funding or even the socio-educational positioning of the school. Research limitations/implications: The findings of this study indicate that high levels of organisational readiness, as defined by the ACE approach, are associated with effective teaching and improvement in student outcomes. The implications are that the ACE provides a framework for what the school leader needs to focus on when whole of school teaching improvement is the goal. The study did not investigate what the school leader did in each school to ready their staff. Practical implications: These findings indicate the importance of leadership in a school and provide an insight into what the school leader needs to focus on when whole of school teaching improvement is the intended goal. This focus can thus be understood as the leader working to ensure all staff members are ACE to the improvement agenda. Social implications: The improvement of educational outcomes is a global goal of governments. In this respect, Organisation for Economic Cooperation and Development (OECD) school systems in particular have linked education system performance and international competitiveness in ways that place pressure on the "black box" of individual schools. Reports, such as the Programme for International Student Assessment and local testing regimes testify that governments and communities are interested in the academic performance of students within and across schooling systems. The benefits of high performing schools contribute to the standard of living of citizens and the well-being of a society more generally. This paper investigates propositions that focus the work of the school leader to achieving such inherent goals. Originality/value: The paper introduces the concept of school readiness. The premise is considered important to the current research because it represents the ability of schools to participate in reform agendas that are characteristic of government policy positions. The "school readiness" approach lies outside the education literature, motivated by the idea that the literature on turning around failing organisations in sectors outside of education provides clear guidelines for reforming schools. The implications for turnaround leadership are particularly encouraging and important particular organisational factors, in common with sectors outside of education, are of significant importance in enhancing teacher motivation, teacher learning and consequential improvements in student outcomes. This paper seeks to add empirical evidence in support of these approaches by adopting what the authors refer as organisational "readiness" for reform developed by Schiemann (2014).